Statistical methods in animal breeding and Bach’s harpsichord concertos - Cantet, Rodolfo Juan Carlos (2010)
Fil: Cantet, Rodolfo Juan Carlos. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina. Universidad de Buenos Aires; Argentina